Carbon capture and utilisation: application of life cycle thinking to process design - Cuellar-Franca, Rosa; Dimitriou, Ioanna; Garcia-Gutierrez, Pelayo; Elder, Rachel H.; Allen, Ray W.K.; Azapagic, Adisa (2015)
Applying life cycle thinking at an early design stage can help engineers to deliver sustainable systems by design. To demonstrate how this can be carried out at a practical level, this paper proposes a simplified methodology for integrating life cycle considerations into process design. Combining flowsheeting and life cycle assessment, it shows how environmental 'hotspots' can be identified and translated into key design targets to improve the sustainability of a system from 'cradle to grave'. The method is applied to a carbon capture and utilisation system using waste CO2 to produce synthetic diesel in a Fischer-Tropsch process. Although the system is energy intensive, applying life cycle thinking helps to make synthetic diesel competitive not only with fossil but also with biodiesel in terms of the climate change impact.